SYARAT WAJIB ZAKAT PROFESI: KAJIAN KOMPARATIF PANDANGAN ULAMA KONTEMPORER DAN IMPLIKASINYA PADA PEMBANGUNAN SOSIAL EKONOMI - Dendi; Nuryati (Kaffah: Jurnal Pendidikan dan Sosio Keagamaan, 2025)
This study aims to conduct an in-depth comparative study of the mandatory requirements for professional zakat based on various contemporary scholars' views, as well as to analyze the implications of its application on the socio-economic development of the Muslim community. Professional zakat, as a relatively new Islamic financial instrument, has given rise to significant differences of opinion among modern fukaha regarding the determination of haul and nisab as well as the method of zakat expenditure. A comprehensive understanding of these varying views is necessary to formulate effective zakat policies that are relevant to the dynamics of the modern economy, where the majority of income comes from monthly salaries or professional services. The research method used is quantitative with a literature study type that focuses on the collection, analysis, and synthesis of secondary data sourced from the works of leading contemporary scholars, scientific journals, fatwas from international fiqh institutions, and books discussing professional zakat. Qualitative data in the form of these legal views were systematically processed to compare the criteria for determining zakat obligations, such as the view that requires haul against the view that requires zakat immediately when income is received. The results and discussion show that there are two main schools of thought regarding the requirements for professional zakat: the mu'asirah view, which strictly applies the requirements of haul and nisab, and the tajdidi view, which requires zakat to be paid immediately after income is received, using the nisab of savings or gold/silver. The implications of this difference are enormous for socioeconomic development. The application of the tajdidi view has the potential to significantly increase the potential for zakat collection, which can then be allocated to poverty alleviation, education, and economic empowerment programs. Therefore, this study recommends the adoption of a more adaptive view to maximize the role of professional zakat as a main pillar in realizing social and economic justice and welfare in society.